Stereoselective pharmacokinetic study of epiprogoitrin and progoitrin in rats with UHPLC–MS/MS method - Xu, Yan (J Pharm Biomed Anal, 2020)
An accurate and precise liquid chromatography–electrospray ionization–tandem mass spectrometry (LC–ESI–MS/MS) method was developed and validated for the pharmacokinetic study of epiprogoitrin and progoitrin, a pair of epimers that can be deglycosylated to epigoitrin and goitrin, respectively. These analytes were administered intravenously or intragastrically to male Sprague–Dawley rats, and the influence of 3(R/S)-configuration on the pharmacokinetics of both epimers in rat plasma was elucidated. The analytes and an internal standard (i.e., sinigrin) were resolved by LC–MS/MS on a reverse-phase ACQUITY UPLC™ HSS T3 column equilibrated and eluted with acetonitrile and water (0.1 % formic acid) at a ﬂow rate of 0.3 mL/min. Quantitation was achieved by applying the multiple reaction monitoring mode, in the negative ion mode, at transitions of m/z 388 → 97 and m/z 358 → 97 for the epimers and sinigrin, respectively. The method demonstrated good linearity over the concentration range of 2–5000 ng/mL (r > 0.996). The lower limit of quantification for epiprogoitrin and progoitrin was 2 ng/mL. The interday and intraday accuracy and precision were within ±15 %. The extraction recovery, stability, and matrix effect were demonstrated to be within acceptable limits. The validated method was thus successfully applied for the pharmacokinetic study of both the epimers. After the rats received the same oral dose of the epimers, the pharmacokinetic profiles were similar. The maximum plasma concentration (C(max)) and AUC values of epiprogoitrin were a bit higher than those of progoitrin, whereas the pharmacokinetic behaviours of the epimers were obviously different upon intravenous administration. The C(max) and AUC values of epiprogoitrin were approximately three-fold higher than those of progoitrin, and the half-life of progoitrin was much shorter than that of epiprogoitrin. The oral bioavailability of progoitrin was 20.1 %–34.1 %, which is three times higher than that of epiprogoitrin.